Implementasi Tahsin (Metode Ummi) Untuk Meningkatkan Kualitas Membaca Al-Qur’an - Mustika, Mulia Intan; Fahyuni, Eni Fariyatul (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This research aims to analyze, understand, and describe the Ummi method developed by TPQ As Syifa, focusing on its implementation at TPQ As Syifa. The research method used is descriptive qualitative, involving data collection through observation, interviews, and documentation. After collecting the data, analysis, data classification, and conclusions were drawn. The results of the study indicate that the Ummi method at TPQ As-Syifa has had a positive impact on improving the quality of Quranic reading among students. The Ummi method involves learning and memorizing the Quran from volumes 1 to 6, with a primary foundation in understanding Tajweed. Understanding Tajweed is crucial in achieving the research goal, which is to ensure the effectiveness of teaching so that students can become Quran readers with a good understanding of Tajweed and can apply it in their daily lives. Thus, the Ummi method at TPQ As-Syifa not only enhances Quranic reading skills but also provides a strong foundation for understanding Tajweed rules, expected to be practically applied in daily life.